2015
DOI: 10.7860/jcdr/2015/11537.5773
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Visfatin Concentration in Response to Non-surgical Periodontal Therapy

Abstract: The results demonstrated that salivary levels of visfatin are reduced after non-surgical periodontal therapy to the levels comparable with those found in healthy individuals. Therefore, the salivary visfatin level may have the potential to be a target marker for assessment of responses to non-surgical periodontal therapy. However, more studies with larger sample sizes are necessary to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
4
9
0
1
Order By: Relevance
“…Then, Raghavendra et al 36 showed that increased GCF visfatin levels in periodontitis reached levels similar to those in healthy individuals after periodontal treatment. In additional studies, this adipokine in saliva was found to be a marker of inflammation in periodontal disease, and the levels in saliva decreased after periodontal treatment 25 , 37 . In this study, the level of visfatin in GCF in patients with periodontitis was higher compared with that of the healthy individuals, which is consistent with these other studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Then, Raghavendra et al 36 showed that increased GCF visfatin levels in periodontitis reached levels similar to those in healthy individuals after periodontal treatment. In additional studies, this adipokine in saliva was found to be a marker of inflammation in periodontal disease, and the levels in saliva decreased after periodontal treatment 25 , 37 . In this study, the level of visfatin in GCF in patients with periodontitis was higher compared with that of the healthy individuals, which is consistent with these other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Visfatin levels in saliva and gingival crevicular fluid (GCF) are reported to increase in periodontal disease and to decrease after periodontal treatment 14,23‐25 . Visfatin is produced in periodontal cells and is regulated by microbial, inflammatory, and biomechanical signals 16 , 26 .…”
mentioning
confidence: 99%
“…In several studies, high levels of visfatin have been reported in saliva, GCF, and periodontal tissue in periodontitis 6,7,41‐43 . In contrast, visfatin GCF and saliva levels have been reported to decrease after NSPT 15–18 . In another study by the present authors’ research group, it was suggested that the microbiologic agents that colonize the subgingival region in periodontitis can increase visfatin expression 19 .…”
Section: Discussionmentioning
confidence: 61%
“…Its role in periodontal inflammation has been demonstrated in several recent studies. Increased levels in saliva and gingival crevicular fluid (GCF) were found to decrease after non‐surgical periodontal therapy (NSPT) 15–19 . Chemerin is another proinflammatory adipokine with a different mechanism 20 .…”
mentioning
confidence: 99%
“…(38,39) A limited number of studies have used visfatin as a potential periodontal marker in saliva, serum and gingival crevicular fluid (GCF) demonstrating that it could be a new reliable periodontal biomarker. (40)(41)(42) It was reported that increased visfatin expression has been associated with a variety of inflammatory diseases. (43,44) Visfatin stimulates the release of proinflammatory cytokines such as TNF-α and IL-8 by peripheral mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%